Non-aqueous electrolyte and lithium ion battery

By using non-aqueous electrolyte in lithium-ion batteries, combined with ingredients such as methyl propionate or ethyl butyrate and lithium hexafluorophosphate, and adjusting the composition and thermal expansion rate of the electrolyte, the cycle performance and high-temperature safety of lithium-ion batteries at high rates are solved. It solves the problem of insufficient performance and achieves the effect of taking into account both magnification performance and safety performance.

CN119340472AActive Publication Date: 2025-01-21SHENZHEN CAPCHEM TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411845104.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-21
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are prone to lithium extraction when circulating at high magnification, resulting in circulating diving failure. At the same time, the safety performance under high temperature and high pressure is insufficient, which limits the promotion of fast-charge electrolyte.

Method used

A non-aqueous electrolyte is used, including methyl propionate or ethyl butyrate as an organic solvent, two different lithium salts, one of which is lithium hexafluorophosphate, and by adjusting the total content of lithium salt, the content of lithium hexafluorophosphate and the electrolyte The thermal expansion rate meets the specific mass percentage and concentration relationship to take into account the rate performance and safety performance of the battery.

Benefits of technology

It improves the cycle performance of lithium -ion batteries at a high rate, reduces the safety hazards of batteries at high temperatures, and enhances the high temperature stability and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a non-aqueous electrolyte and a lithium ion battery. The non-aqueous electrolyte comprises a lithium salt and an organic solvent; according to the non-aqueous electrolyte, at least one carboxylic ester of methyl propionate and ethyl butyrate is used as an organic solvent, two different lithium salts are adopted, and one of the lithium salts is lithium hexafluorophosphate; when the relation among the mass percentage content a of carboxylic ester in the non-aqueous electrolyte, the mass percentage content b of lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte and the thermal expansion rate d of the non-aqueous electrolyte is limited to meet 1.8 < = (10 * d + n * b) / a < = 18, 10 < = a < = 60, 30 < = b < = 98, 0.8 < = n < = 1.5 and 3.2 < = d < = 10, the high rate and high safety characteristics of the battery can be considered; and the potential safety hazard of a high-rate lithium battery product is reduced, and meanwhile, the charging rate of the existing battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a non-aqueous electrolyte and a lithium ion battery having both rate performance and safety performance of the battery. Background Art

[0002] Lithium-ion batteries have been widely used in the fields of 3C digital products such as mobile phones and laptops, as well as new energy vehicles, due to their advantages such as high operating voltage, wide operating temperature range, high energy density and power density, no memory effect and long cycle life. In recent years, the development of lithium-ion batteries has tended towards high energy density, high rate and high safety.

[0003] Under this market trend, battery materials tend to use high-density, low-porosity positive and negative electrode materials and thin-layer separators to increase the proportion of positive and negative electrode active materials in the battery and improve the battery's energy density. However, in this battery system, the porosity is very low, resulting in insufficient diffusion and infiltration of the electrolyte on the electrode, which seriously affects the battery cycle rate, leading to lithium deposition in the battery cycle at high rates, and then causing the battery cycle to fail. In order to develop batteries that take into account both high energy density and high rates, how to design an electrolyte with high ionic conductivity and lithium ion migration number becomes the key; in order to meet the high safety characteristics of the battery, the electrolyte needs to further meet the requirements of good compatibility with the battery under high temperature and high pressure.

[0004] The current market mainly uses two solvents, ethyl acetate and ethyl propionate, to reduce electrolyte viscosity and improve the lithium conductivity of the electrolyte, but this has seriously deteriorated battery safety performance and limited the promotion and use of fast-charging electrolytes. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a non-aqueous electrolyte and a lithium ion battery that take into account both the rate performance and safety performance of the battery.

[0006] The present invention adopts the following technical solutions: A non-aqueous electrolyte comprising a lithium salt and an organic solvent; The organic solvent includes at least one carboxylate selected from methyl propionate and ethyl butyrate; The lithium salt comprises at least two kinds, one of which is lithium hexafluorophosphate; The non-aqueous electrolyte meets the following conditions: 1.8≤(10×d+n×b) / a≤18,10≤a≤60,30≤b≤98,0.8≤n≤1.5,3.2≤d≤10; Wherein, a is the mass percentage of carboxylic acid ester in the non-aqueous electrolyte, in wt%; b is the mass percentage of lithium hexafluorophosphate in the lithium salt, in wt%; n is the total content of lithium salt in the non-aqueous electrolyte, in mol / L; d is the thermal expansion coefficient of the non-aqueous electrolyte, unit: % The testing method of the thermal expansion coefficient of the non-aqueous electrolyte is as follows: placing the non-aqueous electrolyte in a container with a capacity scale, then placing the non-aqueous electrolyte in a high and low temperature test chamber and keeping it at 25°C for 2 hours, reading the volume of the non-aqueous electrolyte and recording it as V1; raising the temperature of the high and low temperature test chamber to 85°C and keeping it at 85°C for 2 hours, reading the volume of the non-aqueous electrolyte and recording it as V2; the thermal expansion coefficient of the non-aqueous electrolyte d=(V2-V1) / V1×100%.

[0007] The non-aqueous electrolyte of the present invention uses at least one carboxylate selected from methyl propionate and ethyl butyrate as an organic solvent, and two different lithium salts, one of which is lithium hexafluorophosphate. The inventors have found through extensive research that when the relationship between the mass percentage a of the carboxylate in the non-aqueous electrolyte, the mass percentage b of the lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte and the thermal expansion coefficient d of the non-aqueous electrolyte satisfies 1.8≤(10×d+n×b) / a≤18, 10≤a≤60, 30≤b≤98, 0.8≤n≤1.5, 3.2≤d≤10, they can jointly affect the rate performance and safety performance of the battery to form an interactive unified whole. It is speculated that methyl propionate and ethyl butyrate have excellent dielectric constants and low viscosity characteristics, which help to balance the rate performance and safety performance of the battery; the high conductivity characteristics of the electrolyte are maintained by controlling the total amount of lithium salts, and the interface film formed by lithium hexafluorophosphate at the negative electrode is used to improve the high-temperature stability of the battery. At the same time, the introduction of other lithium salts further helps the stability of the interface film; the limitation of the thermal expansion rate of the electrolyte can control the high-temperature performance of the battery and prevent safety problems such as battery fires. When the mass percentage of carboxylic acid ester in the non-aqueous electrolyte a, the mass percentage of lithium hexafluorophosphate in the lithium salt b, the total content of lithium salt in the non-aqueous electrolyte n and the thermal expansion rate d of the non-aqueous electrolyte are in a synergistic state, the rate performance and safety performance of the battery can be taken into account. Preferably, the mass percentage a of the carboxylate in the non-aqueous electrolyte, the mass percentage b of the lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte and the thermal expansion coefficient d of the non-aqueous electrolyte satisfy 2.5≤(10×d+n×b) / a≤12.5; more preferably, the mass percentage a of the carboxylate in the non-aqueous electrolyte, the mass percentage b of the lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte and the thermal expansion coefficient d of the non-aqueous electrolyte satisfy 3.2≤(10×d+n×b) / a≤12.5.

[0008] The organic solvent of the present invention is selected from at least one carboxylate selected from methyl propionate and ethyl butyrate. Carboxylate is superior to conventional carbonate solution in improving battery rate performance, but carboxylate is poorly compatible with other components of the battery. Most carboxylates have great corrosion to lithium metal and graphite negative electrode plates at high temperatures, causing battery fires. For carboxylate solvents, methyl propionate has superior high-temperature negative electrode compatibility compared with propyl formate, ethyl acetate, propyl acetate, and propyl propionate; it has higher melting and boiling points than methyl acetate, ethyl formate, and methyl formate, better thermodynamic stability, and excellent dielectric constant and low viscosity characteristics, and is a preferred solvent that takes into account both battery rate performance and thermal safety performance. Ethyl butyrate extends one methyl group on the basis of methyl propionate, has similar dipole moment and polarity, and also has good high-temperature compatibility at the battery negative electrode. Specifically, in some embodiments of the present invention, the mass percentage a of carboxylic acid ester in the non-aqueous electrolyte is 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 24wt%, 25wt%, 27wt%, 30wt%, 32wt%, 35wt%, 38wt%, 40wt%, 42wt%, 45wt%, 48wt%, 50wt%, 52wt%, 55wt%, 58wt%, 60wt% or an intermediate value composed of any two of these values. If the a value is too low, it cannot effectively reflect the improvement of the conductive properties of the electrolyte; if the a value is too high, the thermodynamic stability of the electrolyte will decrease, and the volume expansion of the electrolyte at high temperature will cause uneven distribution of the system. Preferably, the mass percentage a of carboxylic acid ester in the non-aqueous electrolyte is 15wt%~50wt%; more preferably, the mass percentage a of carboxylic acid ester in the non-aqueous electrolyte is 15wt%~30wt%.

[0009] The content of lithium salt is one of the key factors affecting the conductive properties of non-aqueous electrolytes. In order to maintain the high conductivity of non-aqueous electrolytes, in some embodiments of the present invention, the total content n of lithium salts in the non-aqueous electrolyte is 0.8 mol / L, 0.85 mol / L, 0.9 mol / L, 0.95 mol / L, 1.0 mol / L, 1.05 mol / L, 1.1 mol / L, 1.15 mol / L, 1.2 mol / L, 1.25 mol / L, 1.3 mol / L, 1.35 mol / L, 1.4 mol / L, 1.45 mol / L, 1.5 mol / L or an intermediate value composed of any two of these values. If the n value is too low, the electrolyte conductivity is low; if the n value is too high, the anion and cation dissociation is not complete, resulting in a decrease in the number of lithium ion migration and a decrease in conductivity. Preferably, the total content n of lithium salts in the non-aqueous electrolyte is 1.0 mol / L~1.4 mol / L.

[0010] The lithium salt of the present invention comprises lithium hexafluorophosphate, which as a traditional lithium salt can form a LiF-rich SEI interface film at the negative electrode of the battery, thereby improving the high temperature stability of the battery interface; at the same time, the content of lithium hexafluorophosphate in the lithium salt needs to be above 30wt% to ensure the strength of the battery SEI and the interface repair during the cycle storage process; however, the interface film formed by a single lithium hexafluorophosphate cannot support the efficient insertion and extraction of lithium ions at the negative electrode of the battery, so it is necessary to introduce other lithium salts to improve the efficiency of interface lithium conduction. Specifically, in some embodiments of the present invention, the mass percentage b of lithium hexafluorophosphate in the lithium salt is 30wt%, 35wt%, 38wt%, 40wt%, 45wt%, 48wt%, 50wt%, 52wt%, 55wt%, 58wt%, 60wt%, 62wt%, 65wt%, 68wt%, 70wt%, 72wt%, 75wt%, 78wt%, 80wt%, 82wt%, 85wt%, 88wt%, 90wt%, 92wt%, 95wt%, 98wt% or an intermediate value composed of any two of these values. Preferably, the mass percentage b of lithium hexafluorophosphate in the lithium salt is 60wt%~97wt%.

[0011] Specifically, in some embodiments of the present invention, the lithium salt also includes one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiODFB), lithium difluorooxalatophosphate (LiODFP), lithium dioxalatoborate (LiBOB), lithium tetrafluoroborate (LiBF4), and lithium difluorophosphate (LiPO2F2). The present invention combines lithium hexafluorophosphate with any one or more of the above lithium salts to introduce higher content of inorganic components such as Li2O and Li3N to improve the interface lithium conduction efficiency compared with the single addition of lithium hexafluorophosphate. At the same time, the introduction of elements such as B, S, and P can improve the stability of the interface film to a certain extent.

[0012] The thermal expansion coefficient of the non-aqueous electrolyte is a thermodynamic property of the electrolyte at high temperature, which is determined by the overall composition of the non-aqueous electrolyte. Since the maximum temperature rise of the battery during the rate cycle can reach 30~40°C, the inhomogeneity of the temperature inside the battery will cause the inhomogeneity of the system. The greater the thermal expansion coefficient of the electrolyte, the more obvious the dilution phenomenon of the electrolyte in the high temperature area, and the inhomogeneity inside the battery is amplified; at the same time, the intensification of the side reaction at high temperature further causes the consumption of the electrolyte to increase, and the local electrolyte drying up causes the battery to precipitate lithium, resulting in a sudden drop in the cycle capacity and battery fire. Specifically, in some embodiments of the present invention, the thermal expansion coefficient d of the non-aqueous electrolyte is 3.2%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or the intermediate value of any two of these values. Preferably, the thermal expansion coefficient d of the non-aqueous electrolyte is 3.2%~8%.

[0013] For the test method of thermal expansion rate of non-aqueous electrolyte, the present invention sets 85°C as the temperature rise height. Since the 85°C test is the highest temperature in the current conventional battery test, the thermal expansion rate at the extreme temperature is more representative. More specifically, the test method of thermal expansion rate of non-aqueous electrolyte of the present invention is as follows: the non-aqueous electrolyte is placed in a glass bottle with a capacity scale, filled to 2 / 3 of the volume of the container, and then the non-aqueous electrolyte is placed in a high and low temperature test box with a glass observation window, the temperature of the high and low temperature test box is set to 25°C and kept warm for 2h, and the volume of the non-aqueous electrolyte is read from the glass observation window parallel to the concave liquid surface of the non-aqueous electrolyte and recorded as V1; the high and low temperature test box is heated to 85°C at a rate of 5°C / min, and kept warm at 85°C for 2h, and the volume of the non-aqueous electrolyte is read from the glass observation window parallel to the concave liquid surface of the non-aqueous electrolyte and recorded as V2; the thermal expansion rate of non-aqueous electrolyte d=(V2-V1) / V1×100%.

[0014] The thermal expansion rate of non-aqueous electrolyte is closely related to the composition of lithium salt, organic solvent and additives in non-aqueous electrolyte, and can be regulated by adding free low-boiling point solvent, lithium salt and additives with strong polarity. Specifically, the thermal expansion rate of non-aqueous electrolyte is most affected by free solvent molecules. The more free low-boiling point solvent there is, the higher the thermal expansion rate; the larger the anion of lithium salt, the lower its ability to bind with solvent molecules, and the thermal expansion rate of non-aqueous electrolyte will be relatively increased; the more polar additives such as FEC, VC and nitrile will preferentially combine with lithium ions and anions to form a solvent shell, squeeze out solvent molecules, and lead to an increase in free solvent molecules, and the thermal expansion rate will increase accordingly; but since the additive molecules themselves have the characteristics of high boiling point, the overall thermal expansion rate will be reduced to a certain extent, and the thermal expansion rate of electrolyte can be fine-tuned by adding additives.

[0015] Specifically, in some embodiments of the present invention, the conductivity σ of the non-aqueous electrolyte satisfies: 6.5 mS / cm~10 mS / cm.

[0016] Specifically, in some embodiments of the present invention, the organic solvent further includes at least one of a cyclic carbonate solvent, a linear carbonate solvent, a carboxylate solvent, and an ether solvent.

[0017] In some preferred embodiments, the cyclic carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate and butylene carbonate.

[0018] In some preferred embodiments, the linear carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.

[0019] In some preferred embodiments, the carboxylate solvent includes at least one of ethyl acetate, ethyl propionate, propyl propionate, methyl acrylate, ethyl difluoroacetate, methyl acetate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate and ethyl trimethylacetate except methyl propionate and ethyl butyrate.

[0020] In some preferred embodiments, the ether solvent includes at least one of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0021] Specifically, in some embodiments of the present invention, the non-aqueous electrolyte further includes an additive, and the additive includes at least one of a cyclic sulfate ester compound, a sultone compound, a cyclic carbonate compound, a phosphate ester compound and a nitrile compound.

[0022] In some preferred embodiments, the cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate.

[0023] In some preferred embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and propenyl-1,3-sultone.

[0024] In some preferred embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1: ;

[0025] In the structural formula 1 shown, R 21 , R22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group; In some preferred embodiments, the compound represented by structural formula 1 includes at least one of the compounds represented by compounds 1-1 to 1-6 below: Compound 1-1; Compound 1-2; Compounds 1-3; Compound 1-4; Compounds 1-5; Compound 1-6.

[0026] In some preferred embodiments, the phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate and the compound represented by the following structural formula 2: Structural formula 2; In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, or a halogenated hydrocarbon group, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group; more preferably, the compound shown in structural formula 2 includes at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate and diallyl hexafluoroisopropyl phosphate.

[0027] In some preferred embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.

[0028] In some embodiments, based on the total mass of the non-aqueous electrolyte as 100%, the content of the additive is 0.01wt%~10wt%. Preferably, the content is 0.1wt%~5wt%; more preferably, the content is 0.1wt%~2wt%. Specifically, the content of any one of the optional substances in the additive can be 0.01wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.5wt%, 5wt%.

[0029] In a second aspect, the present invention further provides a lithium-ion battery comprising a positive electrode, a negative electrode and the above-mentioned non-aqueous electrolyte.

[0030] The negative electrode includes a negative electrode material layer containing a negative electrode active material. Specifically, in some embodiments of the present invention, the negative electrode material is any one or more of a silicon-based material and a carbon material. The silicon-based material is selected from one or more of a silicon material, a silicon oxide material, a silicon-carbon material and a silicon alloy material; preferably, the silicon material is a nano-silicon material; preferably, the silicon oxide material is a SiOx material, wherein 0≤x<2; preferably, the silicon-carbon material is: a silicon-based material containing silicon and carbon materials, and / or a silicon-based material containing SiOy and carbon materials, wherein 0≤y<2; preferably, the silicon alloy material is a Mg2Si alloy material and / or a Fe2Si alloy material. The carbon material is selected from one or more of artificial graphite, natural graphite, composite graphite, graphene, and hard carbon; preferably, the carbon material is an artificial graphite material.

[0031] Specifically, in some embodiments of the present invention, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductor.

[0032] The negative electrode binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; and one or more of styrene butadiene rubber.

[0033] The negative electrode conductive agent includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.

[0034] Specifically, in some embodiments of the present invention, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer is disposed on the surface of the negative electrode current collector. The negative electrode current collector comprises a metal material that can conduct electrons, and preferably, the negative electrode current collector comprises one or more of aluminum, nickel, tin, copper, and stainless steel.

[0035] Specifically, in some embodiments of the present invention, the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material may include LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z O2, wherein M' is selected from one or more of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from one or more of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1, the positive electrode active material may also include one or more of sulfide, selenide, and halide. More preferably, the positive electrode active material may include LiCoO2, LiFePO4, LiFe 0.4 Mn 0.6 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.5 Co 0.2Mn 0.2 Al 0.1 O2、LiNi 0.5 Co 0.2 Al 0.3 One or more of O2.

[0036] Specifically, in some embodiments of the present invention, the positive electrode further comprises a positive electrode current collector, and the positive electrode material layer is disposed on the surface of the positive electrode current collector. The material of the positive electrode current collector may be the same as that of the positive electrode current collector, which will not be described in detail herein.

[0037] Specifically, in some embodiments of the present invention, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer. The positive electrode binder and the positive electrode conductor may be the same as the negative electrode binder and the negative electrode conductor, respectively, and will not be described in detail here.

[0038] Specifically, in some embodiments of the present invention, the lithium-ion battery further includes a diaphragm, and the diaphragm is located between the positive electrode and the negative electrode.

[0039] The diaphragm may be an existing conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.

[0040] The non-aqueous electrolyte of the present invention uses at least one carboxylate selected from methyl propionate and ethyl butyrate as an organic solvent, uses two different lithium salts, one of which is lithium hexafluorophosphate, and limits the relationship between the mass percentage a of the carboxylate in the non-aqueous electrolyte, the mass percentage b of the lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte, and the thermal expansion coefficient d of the non-aqueous electrolyte to meet 1.8≤(10×d+n×b) / a≤18, 10≤a≤60, 30≤b≤98, 0.8≤n≤1.5, and 3.2≤d≤10, thereby taking into account both the high rate and high safety characteristics of the battery, reducing the potential safety hazards of high rate lithium battery products, and facilitating further improving the charging rate of existing batteries. DETAILED DESCRIPTION

[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0042] Example 1

[0043] The method for preparing a lithium-ion battery in this embodiment comprises the following steps: 1) Preparation of positive electrode sheet: The positive electrode active material lithium cobalt oxide LiCoO2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) were mixed evenly in a mass ratio of 94:3:3, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The slurry was evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with an aluminum lead wire using an ultrasonic welder to obtain a positive electrode sheet.

[0044] 2) Preparation of negative electrode sheet: The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) were mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain the negative electrode slurry. The slurry was coated on both sides of the copper foil, dried, rolled and vacuum dried, and the nickel lead wire was welded with an ultrasonic welder to obtain the negative electrode sheet.

[0045] 3) Preparation of electrolyte: Ethylene carbonate (EC), methyl propionate (MP) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:MP:EMC = 1:1:1, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1 mol / L, and 0.5 wt% of lithium difluorooxalatoborate was added. The thermal expansion coefficient of the electrolyte was tested to be 6.22%.

[0046] 4) Preparation of battery cells: A separator is placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator is wound. The wound body is flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 85°C for 48 hours to obtain a battery cell to be injected with liquid.

[0047] 5) Battery filling and formation In a glove box with a dew point controlled below -40°C, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left to stand for 6 hours. Then, the conventional formation of the first charge was carried out according to the following steps: 0.05C constant current charging for 180 minutes, 0.1C constant current charging for 120 minutes, 0.1C constant current charging for 120 minutes, secondary vacuum sealing, and then further charged to 3.65V at a current constant current of 0.5C, and then charged at a constant voltage until the current dropped to 0.02 C, and after standing for 5 minutes, discharged to 3.0V at a current constant current of 0.5C, to obtain a LiCoO2 / artificial graphite lithium ion battery.

[0048] Examples 2-26 and Comparative Examples 1-9 This embodiment and comparative example are used to compare and illustrate the lithium ion battery disclosed in the present invention, including most of the operating steps in the above-mentioned embodiment 1, and the difference lies in: the composition and content of the organic solvent, lithium salt, and additives in the non-aqueous electrolyte, and the thermal expansion coefficient of the non-aqueous electrolyte, as shown in Table 1.

[0049] Table 1 Group MP content a (wt%) Other carboxylic acid ester types and contents Total lithium salt content n(mol / L) Type and content of the second lithium salt <![CDATA[Percentage b (wt%) of LiPF6 in the total amount of lithium salts]]> Thermal expansion coefficient of electrolyte d(%) (10×d+n×b) / a additive Example 1 29 / 1.05 0.5% LiODFB 96.2 6.22 5.63 / Example 2 10 / 1.05 0.5% LiODFB 96.2 6.01 16.11 / Example 3 15 / 1.05 0.5% LiODFB 96.2 6.43 11.02 / Example 4 50 / 1.05 0.5% LiODFB 96.2 6.95 3.41 / Example 5 60 / 1.05 0.5% LiODFB 96.2 7.16 2.88 / Example 6 29 / 0.80 0.5% LiODFB 95.0 6.27 4.78 / Example 7 29 / 1.00 0.5% LiODFB 96.0 6.20 5.45 / Example 8 10 EB 10% 1.50 <![CDATA[6.0% LiBF4]]> 57.3 3.20 11.8 / Example 9 / EB 60% 1.05 0.5% LiODFB 96.2 5.78 2.65 / Example 10 / EB 10% 1.05 0.5% LiODFB 96.2 5.36 15.46 / Embodiment 11 / EB 30% 1.05 0.5% LiODFB 96.2 5.67 5.26 / Example 12 29 / 1.40 1.0% LiODFB 94.3 6.04 6.63 / Embodiment 13 29 / 1.50 0.5% LiODFB 97.3 5.83 7.04 / Embodiment 14 29 / 1.05 0.8% LiODFB0.39% LiBOB8% LiFSI 30.0 7.78 3.77 / Embodiment 15 29 / 1.05 0.75%LiODFB4.5%LiFSI 60.0 7.20 4.66 / Example 16 29 / 1.05 0.4% LiODFB 97.0 6.22 5.66 / Embodiment 17 29 / 1.05 0.26% LiBOB 98.0 6.23 5.70 / Embodiment 18 18 30% MA 1.05 <![CDATA[0.5% LiODFB0.5%LiPO2F2]]> 92.4 8.00 9.83 / Embodiment 19 15 40% MA 1.05 <![CDATA[0.5% LiODFB1.0% LiBF4]]> 88.6 10.00 12.87 / Embodiment 20 60 / 0.80 0.5% LiODFB0.5%LiBOB4.5% LiFSI 45.0 7.93 1.92 / Embodiment 21 50 / 0.95 0.75%LiODFB4.5%LiFSI 55.8 7.20 2.50 / Embodiment 22 15 40% EB 1.25 2% LiTFSI 95.5 6.81 12.50 / Embodiment 23 10 20% EP 1.30 <![CDATA[0.5% LiODFB1.0% LiBF4]]> 90.8 6.20 18.00 / Embodiment 24 29 / 1.05 0.5% LiODFB 96.2 5.86 5.50 FEC1.5% Embodiment 25 29 / 1.05 0.5% LiODFB 96.2 6.14 5.60 VC1.5% Embodiment 26 29 / 1.05 0.5% LiODFB 96.2 6.08 5.58 HTCN1.5% Comparative Example 1 8 20% EP 1.05 3% LiFSI 77.1 5.91 17.51 / Comparative Example 2 63 / 1.10 0.5% LiODFB 96.4 7.17 2.82 / Comparative Example 3 29 / 0.70 0.5% LiODFB 94.3 6.31 4.45 / Comparative Example 4 29 / 1.60 0.6% LiODFB 97.0 5.77 7.34 / Comparative Example 5 15 / 1.00 9% LiFSI 28.0 8.32 7.41 / Comparative Example 6 29 / 1.05 0.1% LiBOB 99.2 6.22 5.74 / Comparative Example 7 17 55% MA 1.05 0.5% LiODFB 96.2 10.50 12.12 / Comparative Example 8 60 / 0.80 8% LiFSI 20.0 9.03 1.77 / Comparative Example 9 10 / 1.50 0.5% LiODFB 97.3 4.30 18.90 /

[0050] Wherein: MP-methyl propionate, EB-ethyl butyrate, MA-methyl acrylate, EP-ethyl propionate, LiPF6-lithium hexafluorophosphate, LiODFB-lithium difluorooxalatoborate, LiBOB-lithium dioxalatoborate, LiFSI-lithium bis(fluorosulfonyl)imide, LiTFSI-lithium bis(trifluoromethanesulfonyl)imide, LiBF4-lithium tetrafluoroborate, LiPO2F2-lithium difluorophosphate, FEC-fluoroethylene carbonate, VC-vinylene carbonate, HTCN-ethanetrinitrile.

[0051] The lithium ion batteries prepared in the examples and comparative examples were subjected to performance tests as follows: Battery 4C / 4C cycle performance test The lithium-ion battery was placed in a constant temperature environment of 25°C, charged at a constant current of 4 C to 4.45 V, then charged at a constant voltage until the current dropped to 0.02 C, and then discharged at a constant current of 4 C to 3 V. This cycle was repeated 500 times, and the first discharge capacity and the last discharge capacity were recorded.

[0052] The capacity retention rate of the cycle is calculated as follows: Battery capacity retention rate (%) = last discharge capacity / first discharge capacity × 100%; Battery thermal abuse test passed critical stability: a. Conduct the test according to the national standard GB 31241-2022 Safety Technical Specification for Lithium-ion Batteries and Battery Packs for Portable Electronic Products, 7.8 Thermal Abuse Test Specification. Repeat the test on 5 batteries. If all 5 batteries pass the test, it will be recorded as the battery passing the 130°C test. b. If the battery passes the 130℃ test, the temperature in the test chamber is raised by 1℃, and the test steps in a are repeated until the battery catches fire or explodes. The highest test temperature that the battery can pass is recorded as the critical temperature of the battery thermal abuse. c. If the battery fails the 130°C test, the temperature in the test chamber is lowered by 1°C and the test steps in step a are repeated until all five battery tests at the corresponding temperature pass. The test temperature of the battery is recorded as the critical temperature for the battery to pass thermal abuse.

[0053] The performance test results of the lithium-ion batteries prepared in the embodiments and comparative examples are shown in Table 2.

[0054] Table 2 Group Battery capacity retention rate after 500 cycles (%) Battery thermal abuse test passed critical stability (℃) Example 1 85.3 135 Example 2 81.3 135 Example 3 85.1 134 Example 4 85.7 133 Example 5 84.2 132 Example 6 82.3 133 Example 7 85.2 135 Example 8 78.3 140 Example 9 83.9 137 Example 10 80.2 138 Embodiment 11 83.4 137 Example 12 85.0 137 Embodiment 13 81.4 134 Embodiment 14 80.0 136 Embodiment 15 84.3 136 Example 16 85.6 134 Embodiment 17 80.3 135 Embodiment 18 86.5 133 Embodiment 19 82.2 131 Embodiment 20 80.1 133 Embodiment 21 80.1 135 Embodiment 22 84.8 136 Embodiment 23 79.1 133 Embodiment 24 84.3 133 Embodiment 25 80.5 135 Embodiment 26 83.2 136 Comparative Example 1 8.9 131 Comparative Example 2 75.2 120 Comparative Example 3 6.3 126 Comparative Example 4 43.2 127 Comparative Example 5 66.2 133 Comparative Example 6 11.4 133 Comparative Example 7 75.1 123 Comparative Example 8 43.3 125 Comparative Example 9 10.2 134 It can be seen from the test results of Examples 1-26 and Comparative Examples 1-9 in Table 2 that the non-aqueous electrolyte of the present invention uses at least one carboxylate selected from methyl propionate and ethyl butyrate as an organic solvent, includes at least two lithium salts including lithium hexafluorophosphate, and when the relationship between the mass percentage content a of the carboxylate in the non-aqueous electrolyte, the mass percentage content b of the lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte and the thermal expansion coefficient d of the non-aqueous electrolyte satisfies 1.8≤(10×d+n×b) / a≤18, 10≤a≤60, 30≤b≤98, 0.8≤n≤1.5, 3.2≤d≤10, the prepared lithium ion battery has good rate performance and high temperature safety performance.

[0055] It can be seen from the test results of Examples 1-23 that when the relationship between the mass percentage a of the carboxylate in the non-aqueous electrolyte, the mass percentage b of the lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte and the thermal expansion coefficient d of the non-aqueous electrolyte satisfies the corresponding relationship, when any one or more of methyl propionate or ethyl butyrate is used as the organic solvent and combined with other organic solvents, the prepared lithium ion batteries have better rate performance and safety performance.

[0056] It can be seen from the test results of Examples 12-23 that when the relationship between the mass percentage a of the carboxylic acid ester in the non-aqueous electrolyte, the mass percentage b of the lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte and the thermal expansion coefficient d of the non-aqueous electrolyte satisfies the corresponding relationship, when lithium hexafluorophosphate is used in combination with one or more other different types of lithium salts, the prepared lithium-ion batteries have better rate performance and safety performance.

[0057] It can be seen from the test results of Examples 1 and 24-26 that when the relationship between the mass percentage a of the carboxylic acid ester in the non-aqueous electrolyte, the mass percentage b of the lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte and the thermal expansion coefficient d of the non-aqueous electrolyte satisfies the corresponding relationship, the lithium ion battery prepared by further combining with conventional additives has better rate performance and safety performance, indicating that the battery system of the present invention is universal for different additives.

[0058] It can be seen from the test results of Example 1 and Comparative Examples 1-9 that when any of the mass percentage a of the carboxylate in the non-aqueous electrolyte, the mass percentage b of the lithium hexafluorophosphate in the lithium salt, the total content n of the lithium salt in the non-aqueous electrolyte and the thermal expansion coefficient d of the non-aqueous electrolyte is too large or too small, or does not satisfy the relevant relationship, it will affect the rate performance and / or safety performance of the lithium-ion battery, further proving the synergistic effect between the above contents.

[0059] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A non-aqueous electrolyte, characterized in that: The non-aqueous electrolyte comprises a lithium salt and an organic solvent; The organic solvent includes at least one carboxylate selected from methyl propionate and ethyl butyrate; The lithium salt comprises at least two kinds, one of which is lithium hexafluorophosphate; The non-aqueous electrolyte meets the following conditions: 1.8≤(10×d+n×b) / a≤18,10≤a≤60,30≤b≤98,0.8≤n≤1.5,3.2≤d≤10; Wherein, a is the mass percentage of carboxylic acid ester in the non-aqueous electrolyte, in wt%; b is the mass percentage of lithium hexafluorophosphate in the lithium salt, in wt%; n is the total content of lithium salt in the non-aqueous electrolyte, in mol / L; d is the thermal expansion coefficient of the non-aqueous electrolyte, unit: % The testing method of the thermal expansion coefficient of the non-aqueous electrolyte is as follows: the non-aqueous electrolyte is placed in a container with a capacity scale, and then the non-aqueous electrolyte is placed in a high and low temperature test chamber and kept at 25°C for 2 hours, and the volume of the non-aqueous electrolyte is read and recorded as V1; the high and low temperature test chamber is heated to 85°C and kept at 85°C for 2 hours, and the volume of the non-aqueous electrolyte is read and recorded as V2; the thermal expansion coefficient of the non-aqueous electrolyte d=(V2-V1) / V1×100%.

2. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte satisfies the following condition: 2.5≤(10×d+n×b) / a≤12.

5.

3. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage a of the carboxylic acid ester in the non-aqueous electrolyte is 15wt%-50wt%.

4. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage b of lithium hexafluorophosphate in the lithium salt is 60wt%~97wt%.

5. The non-aqueous electrolyte according to claim 1, characterized in that The total content n of lithium salt in the non-aqueous electrolyte is 1.0 mol / L to 1.4 mol / L.

6. The non-aqueous electrolyte according to claim 1, characterized in that The thermal expansion coefficient d of the non-aqueous electrolyte is 3.2% to 8%.

7. The non-aqueous electrolyte according to claim 1, characterized in that The lithium salt also includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium dioxalatoborate, lithium tetrafluoroborate, and lithium difluorophosphate.

8. The non-aqueous electrolyte according to claim 1, characterized in that The organic solvent further comprises at least one of a cyclic carbonate solvent, a linear carbonate solvent, a carboxylate solvent, and an ether solvent; and / or, The cyclic carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate and butylene carbonate; and / or, The linear carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; and / or, The carboxylate solvent includes at least one of ethyl acetate, ethyl propionate, propyl propionate, methyl acrylate, ethyl difluoroacetate, methyl acetate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate and ethyl trimethylacetate except methyl propionate and ethyl butyrate; and / or The ether solvent includes at least one of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

9. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte further comprises an additive, wherein the additive comprises at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound and a nitrile compound; and / or, Based on the total mass of the non-aqueous electrolyte as 100%, the content of the additive is 0.01wt% to 10wt%; and / or, The cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate; and / or, The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; and / or, The cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1: Structural formula 1; In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or, The phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate and the compound shown in the following structural formula 2: Structural formula 2; In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, or a halogenated hydrocarbon group, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group; and / or, The nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.

10. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the non-aqueous electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte solution and lithium ion battery thereof

    CN107681198A

  • High-voltage rate electrolyte with high-and-low temperature performance and lithium ion battery using electrolyte

    CN107706455A

  • High-performance lithium metal battery electrolyte and high-performance lithium metal battery

    CN115810799A

  • High-voltage-resistant electrolyte and lithium ion battery

    CN117013082A

  • Cylindrical lithium ion battery

    CN117096462A